Challenges in the diagnosis and treatment of mucormycosis. (10th March 2018) - Skiada, A; Lass-Floerl, C; Klimko, N; Ibrahim, A; Roilides, E; Petrikkos, G
Abstract: The diagnosis and treatment of mucormycosis are challenging. The incidence of the disease seems to be increasing. Hematological malignancies are the most common underlying disease in countries with high income and uncontrolled diabetes in developing countries. Clinical approach to diagnosis lacks sensitivity and specificity. Radiologically, multiple (≥10) nodules and pleural effusion are reportedly associated with pulmonary mucormycosis. Another finding on computerized tomography (CT) scan, which seems to indicate the presence of mucormycosis, is the reverse halo sign. Microscopy (direct and on histopathology) and culture are the cornerstones of diagnosis. Molecular assays can be used either for detection or identification of mucormycetes, and they can be recommended as valuable add-on tools that complement conventional diagnostic procedures. Successful management of mucormycosis is based on a multimodal approach, including reversal or discontinuation of underlying predisposing factors, early administration of active antifungal agents at optimal doses, complete removal of all infected tissues, and use of various adjunctive therapies. Our armamentarium of antifungals is slightly enriched by the addition of two newer azoles (posaconazole and isavuconazole) to liposomal amphotericin B, which remains the drug of choice for the initial antifungal treatment, according to the recently published guidelines by ECIL-6, as well as those published by ECMM/ESCMID. Despite the efforts for better understanding of the pathogenesis, early diagnosis and aggressive treatment of mucormycosis, the mortality rate of the disease remains high.